Muslim Minority on Learning and Religious Teaching in Manado of North Sulawesi, Indonesia - Wekke, Ismail Suardi (TAWARIKH, 2016)
ABSTRACT: Manado in North Sulawesi, Indonesia is a typical area where Muslim and Christian population are living together in the community. Muslim minority circumstance reflects a condition to contribute. Even though they life in particular situation. Therefore, it is a need to explore Muslim minority formation in some part of Indonesia. The article identifies areas of Muslim minority, in which they launched a learning body for educating Muslim. The research was focused in Manado. In-depth-interview and non-participant observation was conducted to collect data. Two bathcs of data collection was directed during two consecutive years research. Last part of research was completed through three focus group discussions. Furthermore, this article shows that Muslim minority in Manado already establish an excellent educational organization. Started from Al-Qurâan festival, Muslim tried to complement the event with education institution. The community tried to promote education chance and opportunity in expanding community elaboration. Nowadays, the school is not only to educate Muslim society but also it is a part to encounters with surrounding area. In addition, the practices also communicate to local counterpart in providing support and maintenance. Finally, this article concludes that Muslim minority in Manado provide valuable portrait to pay attention on surrounding area. The school stimulates an environment agreement to communicate religious diversity on ethnic community.KEY WORDS: Muslim Minority; Islamic Educational Institution; Ethnic Minority; Good Relationship; Learning and Religious Teaching.About the Author: Ismail Suardi Wekke, Ph.D. is a Senior Lecturer at the STAIN (Sekolah Tinggi Agama Islam Negeri or State Islamic College) Sorong, Jalan Klamono-Sorong Km.17, Klablim, Sorong 98417, West Papua, Indonesia. He can be contacted via his email at: iswekke@gmail.comHow to cite this article? Wekke, Ismail Suardi. (2016). âMuslim Minority on Learning and Religious Teaching in Manado of North Sulawesi, Indonesiaâ in TAWARIKH: International Journal for Historical Studies, Vol.8(1) October, pp.93-106. Bandung, Indonesia: Minda Masagi Press and UIN SGD Bandung, ISSN 2085-0980. Chronicle of the article: Accepted (July 5, 2016); Revised (September 9, 2016); and Published (October 28, 2016).